Co‐packaged datacenter optics: Opportunities and challenges. Issue 2 (22nd March 2021) - Minkenberg, Cyriel; Krishnaswamy, Rajagopal; Zilkie, Aaron; Nelson, David
Abstract: High‐capacity, high‐density, power‐, and cost‐efficient optical links are undoubtedly of critical importance for datacenter infrastructure. However, the optics roadmap has come to a fork in the road: Is it right to continue on the tried and proven path of pluggable modules or is it time to adopt a new deployment model that involves co‐packaged optics? Herein, we aim to shed light on the trade‐offs involved, enabling technologies, paths to adoption, and potential impact on datacenter network architecture.